(untitled) (Eurasian Scientific Herald, 2025)
This article analyzes the impact of microclimatic conditions, timing and working posture on the performance of employees in the field of accounting. The study evaluated the parameters of the microclimate, including air temperature, speed of movement and humidity; hygienic assessment of the working position was carried out. In addition, the work process was timed, and the subjective feelings of employees were studied – the perception of thermal comfort, general well-being and the level of fatigue at the end of the working day. As a result of the conducted research, it was revealed that the working conditions are satisfactory